Application of sol gel technique for glucose oxidase immobilization in biosensor application - Mohd. Nasir, Nashrul Fazli; Ying, Yang; Che Ahmad, Azlan; Kadri, Nahrizul Adib (2006)
A sol gel based biosensor using 3-glycidoxypropyl dimethylethoxysilane, as a silane agent was developed as a novel method for biosensor enzyme immobilization. The key materials applied were tetra methyl orthosilicate (TMOS), and the cross link agent, 3-Glycidoxypropyl dimethylethoxysilane, (GDP). Three compositions with different amount of GDP and glucose oxidase were experimented with the amount of TMOS was kept constant. The first coating consisted of 2mg of glucose oxidase and 20µl of GDP. The second trial involved higher GDP composition which is 100µl. The final trial applied higher content of glucose oxidase which is 12 mg with 20µl of GDP. The result showed that sensors with high composition of crosslink agent coating was capable to exhibit reliable glucose detection. The crosslink agent insufficiency in the first composition failed to provide good attachment for the enzyme on the electrode. Thus, the test was halted after few readings due to the inability of the sensor to detect glucose increment. For the high amount glucose oxidase composition, failure happened due to the deficiency of GDP to retain the enzyme thus contributed to the glucose oxidase leaching. We conclude that adequate amount of crosslink agent is vital for a sol gel based biosensor to function successfully.